A high absorptance wide-band metamaterial absorber with metasurface and low-permittivity dielectric slabs. (1st December 2022) - Ma, Zheyipei; Jiang, Chao; Li, Jiale; Huang, Xiaozhong
Abstract: In this paper, a new wide-band and high-absorption metamaterial absorber (WHMA), consisting of a metasurface (MS), three low-permittivity dielectric slabs, and a metal backplane, is proposed and fabricated. The unit cell of MS is concentric rings loaded with chip resistors. This structure exhibits excellent absorption property and improved stability of oblique incidence, which are difficult to be achieved in previous radar absorbing materials. The functions of MS and different dielectric slabs are analysed. At normal incidence, the simulated results indicate that −10 dB absorption and −20 dB absorption bands cover a bandwidth of 4.8–14.3 GHz and 5.70–13.57 GHz, respectively. The measured results show that −10 dB and −20 dB absorption are achieved with the bandwidth of 4.6–16.3 GHz and 5.5–14.4 GHz respectively at normal incidence; below 50° angle of oblique incidence, WHMA can still have wide-band −10 dB absorption. The agreement between simulation and measurement validates the proposed design. Finally, since the structure is made of foam and thin dielectric layers, the area density is relatively low.